Measurement of vapor-liquid equilibria for the binary mixture of propane (R-290) plus isobutane (R-600a) - LIm, JS; Ho, QN; Park, JY; Lee, BG (AMER CHEMICAL SOC, 2004)
Isothermal vapor-liquid equilibria data for the binary mixture R-290 + R-600a at four equally spaced temperatures between (273.15 and 303.15) K were measured by using a circulation-type equilibrium apparatus. The experimental data were correlated with the Carnahan-Starling-De Santis equation of state (CSD-EOS) and the Peng-Robinson equation of state (PR-EOS) combined with the Wong-Sandler mixing rule. The data calculated by these equations of state are in good agreement with experimental data. Azeotropic behavior was not found in this mixture.
Keywords: MIXING RULE; STATE; EQUATION